Investigation of expression of high-molecular substances as the consequence of exposure to laser light on the organism of earth worm Eisenia veneta - Timchy, K. I.; Smetanin, V. T.; Sidashenko, O. I.; Kilochek, T. P.; Nedzvetskii, V. S. (Problems of Environmental Biotechnology, 2017)
The effect of laser light on the content of fractions of soluble and a membrane protein in tissues of worms of parental forms and generation F1 of the species Eisenia veneta was estimated. Studies have shown changes in the protein spectrum in the tissues of animals of the F1 generation relative to the parent forms that were differently exposed to laser light.